Unpacking the Authentic Nursing Terms: A Pilot Study to a Corpus-Based English Indonesian Nursing Dictionary - Komilie Situmorang; Santa Maya Pramusita; Hananto Hananto (Malahayati Nursing Journal, 2025)
ABSTRACT Authentic nursing terms help nurses, lecturers, and students give accurate and excellent nursing care. However, there is no existing nursing dictionary that has facilitated specific English-Indonesian nursing terms. This study was a pilot study to develop a nursing corpus to establish bank data and build an authentic nursing dictionary through nursing discourses like journals, clinical notes, scoping, systematic reviews, and commentaries The research utilized corpus linguistics as its working methodology by using purposive sampling to collect 651 articles from seven high-impact nursing journals. The open-access journal PDFs were downloaded and converted into TXT. The TXT files were imported to a concordance software package, Antconc, creating a corpus of 3.613.424 tokens. The frequency analysis resulted in 53.105 words, and cluster analysis was performed to find the word and phrase patterns. The finding revealed a 5000-word pioneer of nursing authentic terms. Later, the words will be translated, and sentence examples will be provided in English and Bahasa Indonesia. These nursing terms will be an excellent source for teaching English to nurses, for the International Nursing Program, nurses in practice, staff, and students in nursing care. Keywords: Antconc, Corpus Linguistics, Dictionary, Nursing Dictionary, Nursing                  terms